The etiology and clinical features of non-CAH primary adrenal insufficiency in children - Liu, Ziqin; Liu, Yi; Gao, Kang; Chen, Xiaobo (Frontiers in Pediatrics, 2022)
Background The most common cause of primary adrenal insufficiency (PAI) in children is congenital adrenal hyperplasia; however, other genetic causes occur. There is limited epidemiological and clinical information regarding non-CAH PAI. Methods Data for patients diagnosed from January 2015 to December 2021 at a tertiary hospital in northern China were retrospectively analyzed. We excluded those with CAH, which is the most common pathogenic disease among PAI patients. Next-generation sequencing was used for genetic analysis. Results This retrospective study included 16 children (14 males and 2 females) with PAI. A genetic diagnosis was obtained for 14/16 (87.5%) individuals. Pathogenic variants occurred in 6 genes, including ABCD1 (6/16, 37.5%), NR0B1 (4/16, 25.0%), NR5A1/steroidogenic factor-1 (2/16; 12.5%), AAAS (1/16, 6.25%), and NNT (1/16, 6.25%). No genetic cause of PAI diagnosis was found in 2 girls (2/16, 12.5%). Conclusions Causes of PAI in children are diverse and predominantly affect males. Most PAI in children is congenital, and ABCD1 gene defects account for the largest proportion of PAI cases. Whole-exome sequencing is a tool for diagnosis. However, diagnoses are unclear in some cases.